Attitudes toward bullying and bullying perpetration in Belgrade secondary schools - Adrijana, (Norma, 2026)
This paper presents the results of a cross-sectional study examining the association between students’ attitudes toward bullying and bullying perpetration, as well as differences in these attitudes by sex, grade level, and students’ role in bullying. The study was conducted during the 2020/2021 school year on a sample of 2,008 students from grades 1–4 attending 19 secondary schools in Belgrade. The findings showed that higher levels of bullying perpetration were associated with greater approval of bullying. Girls showed lower levels of approval of bullying than boys, while no grade-level differences were found. With regard to bullying roles, bullies and bully-victims showed greater approval of bullying, whereas uninvolved students and victims expressed the strongest opposition to such behavior. The findings highlight the importance of preventive activities targeting bullies and bully-victims, particularly through challenging beliefs that justify or normalize bullying and promoting socio-emotional competencies.
Keywords: bullying; attitudes toward bullying; bullying perpetration; roles of students in bullying